Pemanfaatan Potensi Lingkungan dalam Rangka Pencegahan Stunting di Desa Berakit Kabupaten Bintan - Suryaningsih, Suryaningsih; Niko, Nikodemus; Wahyuni, Sri; Syafitri, Rahma; Valentina, Annisa; Qurdiansyah, Adhitya; Eka Saputra, Alfian; Fauziandi, Ronald; Novita Ulfa, Rosi; Medisa, Rani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Pupose: This PKM activity aims to explore the potential of the environment in stunting prevention efforts in Berakit Village, Bintan Regency. Methodology: The methods used were socialization and lectures. Data was collected from various sources, including families with children under five, health workers, and community leaders. Results: The results of this PKM show that utilizing yard land to grow vegetables and fruits, as well as freshwater fish farming, can improve children's nutritional intake. In addition, health education programs that actively involve the community have proven effective in increasing knowledge and awareness about the importance of balanced nutrition. Environmental factors, such as the availability of clean water and good sanitation, also play a significant role in stunting prevention. Conclusion: Maximum utilization of local environmental potential and active community participation are the keys to success in reducing the prevalence of stunting in Berakit Village, Bintan Regency. Limitations: Although the stunting prevention program in Berakit Village has shown positive results, there are still some limitations, such as limited resources, funding sustainability, and challenges in changing the mindset of the community as a whole. In addition, the long-term effectiveness of this intervention still needs to be further evaluated. Contribution: The results of this PKM can be a reference for local governments and other stakeholders in designing stunting prevention strategies based on environmental potential.